ULAMA TIMUR TENGAH DAN ISLAMISASI ACEH: STUDI PENDIDIKAN SEJARAH TENTANG OTORITAS SIMBOLIK DAN REALITAS HISTORIS - Abdul Ghani; Ja'far Nasution; Maisura; Juliana Putri; Maitanur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the strong popular narrative that positions Middle Eastern clerics as the dominant actors in the Islamization of Aceh without critical verification of contemporary historical evidence. This study aims to analyze the relationship between the symbolic authority of Middle Eastern clerics and the historical reality of the Islamization of Aceh, as well as its implications for history education. The method used is qualitative research with a critical history approach and intellectual historiography combined with a history education perspective, through analysis of primary sources in the form of classical Acehnese manuscripts, foreign traveler's notes, archaeological and epigraphic evidence, and secondary sources from contemporary academic studies. The results of this study indicate that the claim of dominance of Middle Eastern ulama in the early phase of the Islamization of Aceh in the 12th–14th centuries CE is not supported by contemporary historical evidence, but rather is a retrospective symbolic construction in the historiography of the sultanate. The role of Middle Eastern ulama only became significant in the 16th–17th centuries in the context of the consolidation of the Aceh Darussalam Sultanate, especially as agents of legitimacy of state orthodoxy and ideology. The research findings also emphasize the centrality of local ulama and Nusantara networks in the production, transmission, and adaptation of contextual Islamic knowledge. The implications of this study emphasize the importance of a critical and multi-perspective approach in history education so that the Islamization of Aceh is understood as a complex, networked, and local agency-based historical process, rather than a linear, top-down narrative.